Morfologia e sedimentação de praia estuarina Amazônica (Marahú - Ilha de Mosqueiro/PA) - RAMOS, Carolina Costa (2018)
Estuarine beaches are intertidal deposits of sand, gravel or mud located on the banks of estuaries. Marahú Beach, on Mosqueiro Island, is characterized as estuarine beach being subject to morphological changes according to the seasonal characteristics of the region. The objective of this work was to analyze the morphosedimentary variation and the vulnerability to coastal erosion in the east and west sectors of the beach, during the tides of equinoctial syzygium (09/30/2016) and quadrature (09/11/2016), trying to find out if the effects of erosion and / or deposition of sediment remain continuous during the less rainy season of the Amazon, even in the change of the state of the tide during a lunar cycle. The methodology consisted of: (1) acquisition of topographic data through beach profiles; (2) sampling of surface sediments; (3) laboratory analysis of sediments for granulometric separation; and (4) processing of the data obtained in situ and in the laboratory through the software Grapher, Surfer, Sysgran and Excel. The results show that the beach of Marahú, during the equinoctial tidal wave of the September campaign, presented a incremental phase, with higher sedimentary volume in the beaches profiles, and predominance of average sand in both sectors. During the study period the erosive phase occurred during the quadrature tide, in the November campaign, considered as a transition month for the rainiest period. The proximity to this more erosive period may have resulted in the loss of sedimentary volume from the beach from September to November. There is an increase in the occurrence of thick sediments in this last month and a decrease in fines. The beach of Marahú presented morphodynamic classification of beach intermediate to reflective, according to the sector and period analyzed, since it is marked by promontories and rocky pontoons at its extremities, as well as rocky outcrops in some profiles and this ends up influencing the morphology, hydrodynamics and local sediment transport.